Capital structure, working capital, and governance quality affect the financial performance of small and medium enterprises in Taiwan - Anh-Huyen Vu Thi; The-Dong Phung (Journal of Risk and Financial Management, 2021)
This study examines the impact of capital structure, working capital, and governance quality on the financial performance of small- and medium-sized enterprises in Taiwan using a sample of more than 2000 firms from the Taiwan Economic Journal (TEJ) during the 24-year period of 1995-2018. Panel data are used to create statistics for the regression model. The result shows that a firm's capital structure, represented by the debt ratio, has a significantly negative impact on the firm's financial measures (return on assets (ROA) and return on equity (ROE)), where the working capital, represented by the cash conversion cycle (CCC), has a negative impact and governance quality, represented by the board size, cash dividend distribution, and the percentage of directors, has different impacts.
Keywords: C58; D24; E22; 330; capital structure; financial performance; governance quality; working capital